(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
The purpose of this article is to establish a connection between key policy actors and significant policy issues regarding religion in public discourse and peacebuilding within a broader context. The challenge lies in addressing the dilemmas surrounding whether discussions about religion, its impact on younger generations, and its role in peacemaking are solely influenced by religious factors, or if other social and political actors play a role as well. Through our research, we have identified ongoing political processes that have the potential to enhance religious dialogue and peacemaking on various levels. This mapping of actors and processes has been informed by literature, established academic and social networks like Culturelink (a Network of Networks for Research and Cooperation in Cultural Development, established by UNESCO and the Council of Europe), web searches, and interviews with stakeholders. The result of this analysis is a comprehensive list of over 300 actors documented in the RETOPEA Horizon 2020 project. We contend that current political processes offer opportunities to strengthen dialogue, which is more robust in some European countries but lacking in others when it comes to addressing issues related to the resurgence of religion in international politics and peacebuilding efforts.